Klaim Kebenaran Agama: Sebuah Refleksi Komparatif Pemikiran John Hick dan Alvin Platinga - Lidia Krismawati; Eko Winarto; Kevin Marthin; Polina Palayukan; Oda Lase; Tryo Agus Purwanto (Sekolah Tinggi Teologi Injili Jakarta, 2023)
Religion should be a pioneer in building an ethical attitude in viewing every difference amid multiculturalism and religious plurality. Claims of truth that are unique to every religion should be a legacy that can become a bridge for adherents of religions to have higher and better ethical awareness. Distorting truth claims, as proposed by Hick, is not a good solution for building diversity. Because truth claims are inherited from a belief that should be maintained and deepened. The problem of tensions between religious adherents is not due to truth claims but the need for more awareness of every religious adherent to ethical values in building interfaith tolerance. To build this ethical awareness, Plantinga proposes a bridge in the realm of shared awareness of God's existence. This awareness encourages every religious adherent to respect the existence of other religious people different from God's creation. In addition to awareness of God's existence, Yunus added this bridge in the Indonesian context to build community culture, which contains ethical awareness to respect adherents of different religions, as proposed by Darmaputera and Suseno. AbstrakAgama seharusnya menjadi pionir dalam membangun sikap etis dalam memandang setiap perbedaan ditengah multikultural dan pluralitas agama. Klaim kebenaran yang menjadi keunikan setiap agama seharusnya menjadi warisan yang dapat menjadi jembatan bagi penganut agama untuk memiliki kesadaran etis yang semakin tinggi dan baik. Mendistorsi klaim kebenaran seperti yang digagas oleh Hick bukanlah solusi yang baik dalam membangun keberagaman. Sebab klaim kebenaran merupakan warisan dari sebuah keyakinan yang seharusnya diperlihara dan diperdalam. Persoalan adanya ketegangan antarumat beragama pada dasarnya bukan karena klaim kebenaran tetapi kurangnya kesadaran setiap penganut agama terhadap nilai etis dalam membangun toleransi antarumat beragama. Untuk membangun kesadaran etis tersebut, Plantinga mengusulkan jembatan dalam ranah kesadaran bersama akan keberadaan Allah. Kesadaran ini mendorong setiap penganut agama menghargai keberadaan umat agama yang lain yang berbeda sebagai ciptaan Allah. Selain kesadaran akan keberadan Tuhan, jembatan tersebut dalam konteks Indonesia juga ditambahkan oleh Yunus dalam bangunan kultur masyarakat, yang di dalamnya mengandung kesadaran etis untuk menghargai penganut agama yang berbeda, seperti yang diusulkan oleh Darmaputera dan Suseno.